PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS VI SDN 013 LUBUK KEMBANG SARI KECAMATAN UKUI - Muhroni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the lack of Civics (PKn) student learning outcomes, which is due to a lack of significance in the teacher's learning approach. The teacher gives no concrete examples and is far from environmentally friendly, resulting in passive students in participating in learning. This study is a class action research that aims to improve learning outcomes in Civics, as well as improving the learning activities of teachers and students using a contextual approach to teaching and learning. Research was conducted during two cycles at SDN 013 Lubuk Kembang Sari Kecamatan Ukui, with research subjects being students of class VI. Data collection techniques used in this study were observation techniques, test engineering, and technical documentation. The analysis technique used is descriptive analysis. Based on the results of research and discussion, it was found that the learning outcomes of students have increased in each cycle, which is strengthened by the results that have been raised previously, namely: (1) the early mastery learning outcomes of Civics Education students gained is 45%; (2) in the first cycle, completeness of PKn learning outcomes of students increased by 70%; and (3) in the second cycle, completeness of PKn learning outcomes of students increased by 80%. This indicates that the classical completeness has been reached, in which the research is successful if the completeness achieved 80% of students obtaining a minimum value of 65. Based on the results and the discussion, it can be concluded that the application of a contextual teaching and learning approach can improve student learning outcomes in PKn Class VI SDN 013 Lubuk Kembang Sari Kecamatan Ukui.